Effectiveness of Subconjunctival Cyclosporine in Treatment of Acute Allergic Conjunctivitis in a Rat-Model - Awara A; Atiba A; Helal D; Elbedewy H (Clinical Ophthalmology, 2020)
Amr Awara,1 Ayman Atiba,2 Duaa Helal,3 Hazem Elbedewy1 1Ophthalmology Department, Tanta University, Tanta, Egypt; 2Department of Surgery, Anesthesiology and Radiology, Faculty of Veterinary Medicine, Kafrelsheikh University, Kafrelsheikh, Egypt; 3Pathology Department, Tanta University, Tanta, EgyptCorrespondence: Amr AwaraOphthalmology Department, Tanta University, Tanta 31511, EgyptTel +2-01274005384Fax +20403415008Email amrawara@gmail.comBackground: Eye allergy is widely spread worldwide. The treatment includes topical anti-histamines, steroids and non-steroidal drugs. Steroids are the first choice by many ophthalmologists, but unfortunately they may cause serious side effects. Cyclosporine A (CsA) is an immunomodulator drug that can improve eye allergy and reduce the need for steroids; however, topical preparation of CsA is difficult because of the lipophilic nature of the drug.Methods: An experimental study included 16 rats with induced allergy were divided into 2 groups. Group 1: allergic non-treated (6 rats), and Group 2: allergic treated with 0.5 mL subconjunctival CsA 1% (10 rats). Half of each group was sacrificed at 24 hrs and the other half at 1 week. Conjunctival hyperemia and eosinophilic cell count were assessed at each time.Results: Group 2 (CsA treated) showed significantly lower hyperemia score and eosinophilic count at both 24 hrs and 1 week. No ocular complications were noted.Conclusion: Subconjunctival CsA was safe and effective in treating ocular allergy through improving conjunctival hyperemia and reducing eosinophilic cell count with no significant ocular side effects.Keywords: eye allergy, cyclosporine A, eosinophilia, subconjunctival